Explicitation strategies of STTs by beginner and professional translators interpreted by relevnce theory - Veresné Valentinyi, Klára (Acta Carolus Robertus, 2022)
In this paper, we present a study in which we investigated the explicitation strategies of beginner, inexperienced and practicing, professional translators in sight translated texts (STTs). Research shows that translated texts (TTs) are longer than non-translated texts (non-TTs) and parallel texts. The reason for this is that translators explicate, i.e. they explain the hidden, implicit message of the text. The strategies of explanation, insertion, repetition, paraphrasing are used as explicitation strategies. One of the reasons for explicitation is that the target language reader has different cultural and professional backgrounds, consequently, they may not always know the background of the source language text, or the original message of the source language text may not be clear enough, therefore, the translator has to explain it. The other reason is that translators seek to be safe, so they will explain the implicit content even when it is not necessary. The study examined the sight translation strategies of beginner and professional translators, as it was assumed that both groups use explicitation strategies, and that they use the same explicitation strategies, since the use of explicitation strategies is a feature of all translations, regardless of the level of experience of the translator. Our research results supported our hypotheses, i.e. the same explicitation strategies appeared in the sight translated texts by beginner and professional translators. However, it has also been found, that beginner, inexperienced translators use more repetition and paraphrasing, which is explained by their inadequate translator competences.
Keywords: lack of sight translation competences; explicitation strategies; repetition; explanation; paraphrasing; different cultural background